2015
DOI: 10.1007/s40262-015-0240-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacokinetic/Pharmacodynamic Modeling of Filgotinib (GLPG0634), a Selective JAK1 Inhibitor, in Support of Phase IIB Dose Selection

Abstract: Background and ObjectivesFilgotinib (GLPG0634) is a selective inhibitor of Janus kinase 1 (JAK1) currently in development for the treatment of rheumatoid arthritis and Crohn’s disease. While less selective JAK inhibitors have shown long-term efficacy in treating inflammatory conditions, this was accompanied by dose-limiting side effects. Here, we describe the pharmacokinetics of filgotinib and its active metabolite in healthy volunteers and the use of pharmacokinetic–pharmacodynamic modeling and simulation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(142 citation statements)
references
References 9 publications
6
134
0
Order By: Relevance
“…A fast onset of effect was observed for ACR20/50/70 and DAS28 (CRP) responses, along with improvements in HRQoL (HAQ-DI); in addition to the convenience of oral administration, rapid action may facilitate effective treat-to-target strategies without the need for bridging glucocorticoids. The filgotinib doses studied and the similar efficacy noted between the once-daily and twice-daily dosing regimens are in line with the previously reported pharmacokinetic and pharmacodynamic effects of filgotinib and its major metabolite, both of which selectively inhibit JAK1 13. Although there was a numerical trend towards better efficacy results with the 200 mg dose given as 100 mg twice daily versus 200 mg once daily, this trend did not extend to the next (lower) dose level of 100 mg, where the reverse trend was observed, such that the once-daily schedule generally performed better than the split dose.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A fast onset of effect was observed for ACR20/50/70 and DAS28 (CRP) responses, along with improvements in HRQoL (HAQ-DI); in addition to the convenience of oral administration, rapid action may facilitate effective treat-to-target strategies without the need for bridging glucocorticoids. The filgotinib doses studied and the similar efficacy noted between the once-daily and twice-daily dosing regimens are in line with the previously reported pharmacokinetic and pharmacodynamic effects of filgotinib and its major metabolite, both of which selectively inhibit JAK1 13. Although there was a numerical trend towards better efficacy results with the 200 mg dose given as 100 mg twice daily versus 200 mg once daily, this trend did not extend to the next (lower) dose level of 100 mg, where the reverse trend was observed, such that the once-daily schedule generally performed better than the split dose.…”
Section: Discussionsupporting
confidence: 86%
“…Filgotinib (GLPG0634/GS-6034) is a potent and selective inhibitor of JAK1,10–12 currently under investigation for the treatment of RA and inflammatory bowel disease. Pharmacokinetic–pharmacodynamic studies of filgotinib and its active metabolite indicate that both moieties contribute to pharmacodynamic effects, resulting in a relatively long duration of JAK1 inhibition,13 suggesting that filgotinib has the potential to be active not only in twice-daily dosing but also in a once-daily regimen. The efficacy and safety of filgotinib in patients with RA has previously been investigated in two 4-week phase IIa studies;14–16 results from these studies informed the design of this phase IIb dose-finding study.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy and safety of filgotinib in patients with RA has previously been investigated in two short-term phase IIa studies, as add-on treatment to MTX, which suggested that filgotinib has the potential to be effective when administered as a once-daily dosing regimen . 11–13 In pharmacokinetic-pharmacodynamic studies, filgotinib was shown to have a terminal half-life (t 1/2 ) of 5–11 hours with an active metabolite that has a t 1/2 of 21–27 hours; both moieties contribute to the pharmacodynamic effects and together provide a relatively long duration of JAK1 inhibition,10 supporting further investigation of a once-daily dosing regimen.…”
Section: Introductionmentioning
confidence: 99%
“…The reason we chose to use filgotinib, which is in an ongoing clinical trial for the treatment of rheumatoid arthritis and Crohn disease (17, 34), over momelotinib, which is in an ongoing clinical trial in combination with trametinib (NCT02206763) or erlotinib (NCT02206763) for the treatment of NSCLC, is that momelotinib would have had off-target activities (35). In other words, by using filgotinib instead of momelotinib, we were able to ensure more complete inhibition of JAK1 activation at doses that did not exhibit off-target effects.…”
Section: Resultsmentioning
confidence: 99%
“…In clinical trial, the combination of JAK1/2 inhibitor ruxolitinib with erlotinib did not demonstrate dramatic effect in patients with acquired erlotinib resistance in recent study (44), while the sample size was small and the results were still controversial. On the other hand, filgotinib is an oral selective JAK1 inhibitor, and showed encouraging safety and efficacy in clinical studies in patients with rheumatoid arthritis (17, 34, 45). Selective inhibition of JAK1 also may offer favorable safety and clinical efficacy in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%